2002
DOI: 10.1238/physica.regular.065a00056
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine Structure and Isotope Shift of Osmium I

Abstract: Laser induced fluorescence spectroscopy has been applied to measure the hyperfine structure and isotope shift of osmium I spectral lines in the visible range. Precise values for the hyperfine structure constants A and B of the most abundant odd mass isotope 189Os and the level isotope shift of altogether 43 excited energy levels were determined evaluating the measurements. Osmium in its natural abundance as well as an enriched sample of 189Os were used during the experiments. Additionally, a parametric analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…These values can be used to determine the line and level shifts for any pair of neutral osmium isotopes. Comparisons with the experimental fine-structure level shifts by Kröger et al [121] for the isotope pair 190,192 Os I revealed good agreement with our theoretical predictions. …”
Section: Sixth Row Elementssupporting
confidence: 88%
“…These values can be used to determine the line and level shifts for any pair of neutral osmium isotopes. Comparisons with the experimental fine-structure level shifts by Kröger et al [121] for the isotope pair 190,192 Os I revealed good agreement with our theoretical predictions. …”
Section: Sixth Row Elementssupporting
confidence: 88%
“…Further measurements, using radiogenic Os-enriched samples, were performed by Guthörhlein et al (1961Guthörhlein et al ( , 1969 and by Himmel (1968). The hyperfine structure and isotope shifts of many levels and lines in Os I were investigated by Kröger et al (2002) using LIF spectroscopy.…”
Section: Atomic Structure and Spectra Of Os I And Os Iimentioning
confidence: 99%
“…The partition functions are taken from Irwin (1981). The isotopic structure as well as the hyperfine structure of 189 Os have been taken into account, using data from Blaise & Wyart (1989) and Kröger et al (2002). Among all the lines examined, only three (at 326.7945, 330.1559 and 442.0468 nm) were retained for the final analysis.…”
Section: A New Solar Abundance For Osmiummentioning
confidence: 99%
“…For example laser induced fluorescence spectroscopy has been applied to measure IS and hfs of Os I spectral lines in the visible range [5]. We have also to mention that other sophisticated measurements of the isotope shifts of the stable 184,[186][187][188][189][190]192 Os isotopes have been made using the crossedbeams technique in Manchester [6]: atomic beams of Os were produced by laser ablation of pills of compressed natural Os powder whose diameter and thickness were 5 mm and 3 mm.…”
Section: Introductionmentioning
confidence: 99%
“…They used the non-relativistic Hartree-Fock method. In opposite we propose in the present work to use the relativistic Dirac-Hartree-Fock method to analyse experimental data of Os I isotope shift found in the literature without any theoretical background [5].…”
Section: Introductionmentioning
confidence: 99%